THE SITUATION OF LYMPHATIC FILARIASIS IN THE MUNICIPALITY OF PAULISTA, PERNAMBUCO, BRAZIL - Batista do Nascimento, Jamerson; Brandão, Eduardo; Diogo da Silva, Fabio; Damo Bernart, Fabiana; Rocha, Abraham (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Cases of Lymphatic Filariasis (LF) have been notified since 1959 in the municipality of Paulista, yet it is still considered an LF-free area. The purpose of this study was to describe the situation of Paulista Health Department. The data were gathered via antigenic surveys carried out in the town, using POC-ICT-AD12 tests. A total of 1,000 individuals, aged 10 and over, were examined in the neighborhoods of Mirueira, Engenho Maranguape, Janga and Maranguape II (250 individuals in each district). Among the individuals evaluated, seven (0,7%) tested positive for antigens using CFA POC-ICT-AD12, 5 out of 250 (2.0%) in the Engenho Maranguape neighborhood and 2 out of 250 (0.8%) in Janga. In this group, one particular individual presented microfilaremia, quantified at 5 Mf/mL. These results suggest that the municipality of Paulista might be a “silent” source of LF continuous transmission, fact that could impact negatively on the goals of the GPELF program meant to provide certification of parasitic disease control and elimination by the year 2022.